Providing refugee: the value of domestic violence shelter services - Chanley, Sharon A.; Campbell, Healther E.; Chanley, Jesse J. Jr. (2001)
This study is a social cost-benefit analysis of domestic violence shelter services. In conducting the analysis, the authors distinguish between short-term and longer-term program costs and benefits. They obtained estimates of several of the short-term costs and benefits and used these figures for their quantitative analysis. They then discuss the potential longer-term costs and benefits of shelter programs but do not monetize these effects. The costs of domestic violence shelter services include operating expenses and public assistance for women and children. The benefits of the domestic violence shelter services include assaults averted and mental health benefits. The authors find that domestic violence shelter services have social benefits that significantly outweigh the social costs. The minimum net social benefit of the domestic violence shelter program is $3,494.934 and the minimum benefit cost ratio is 4.6. - Reproduced.
Keywords: Domestic violence